Exploring the schoolyard: potentials for creating a learning-rich environment at Bergman Elementary School - Talbert, Scot Boyd (Kansas State University, 2011)
The landscapes that surround our elementary schools today do very little to support the education being taught in the classrooms, and often fail to meet the most basic needs of children. This is due to a myriad of different reasons, such as budget-tight school districts spending very little of their resources on outside learning environments, fear of litigation leading to sterile and lifeless schoolyards, and lack of time and resources for educators to implement desired changes. Children learn through direct interactive experience and, as a result, they need complexity and variety in the landscape to stimulate their imaginations and promote self-guided learning. A natural outdoor environment is ideally suited for both interactive learning and a diversity of experiences. Many schools are missing an opportunity to make their outdoor spaces into interactive learning environments. This report explores the issues and opportunities to create stimulating environments at Frank V. Bergman Elementary School in Manhattan, Kansas. Numerous studies have identified the benefits of interactive natural environments on children’s development and academic performance(Moore and Wong 1997; Louv 2008; Bell and Dyment 2006;Fjortoft 2001; Malone and Tranter 2003). Building upon this research, goals and objectives for Bergman’s schoolyard are outlined that focus on creating a positive learning environment for all students, supporting school curriculum, encouraging interaction with nature, and linking the schoolyard to the surrounding community. A master plan for Bergman’s schoolyard is presented. The plan addresses the current needs of the schoolyard to improve accessibility. In addition, the master plan presents ideas for strengthening the circulation pathways to connect all areas of the schoolyard together, developing outdoor classroom spaces with connections to state academic standards, and incorporating community amenity features into the landscape. Recommendations for construction, maintenance, and phasing are suggested.
Keywords: Schoolyard; Learning; Children; Education; Education, General (0515); Landscape Architecture (0390)